Pembentukan Portofolio Saham Yang Optimal Dengan Menggunakan Model Markowitz Sebagai Dasar Penetapan Investasi Saham Pada Jakarta Islamic Index - Ali Ahir Rambe; Tri Rachmat Riski (Jurnal Penelitian Dan Pengkajian Ilmiah Sosial Budaya, 2022)
This research was conducted on the basis of the increasing number of investors who choose to invest their funds in stocks, which is indicated by the increasing positive sentiment on stock investments compared to other investments. Formation of a portfolio with the Markowitz Model is one model that can be used to form a portfolio, because with this model a portfolio can be formed according to the characteristics of the desired investment and the objectives to be achieved. The results of this study indicate that there are eleven stocks that are included in the optimal portfolio with the Markowitz model on the Jakarta Islamic Index, including: PT. Aneka Tambang Tbk (ANTM), PT. Ciputra Development Tbk (CTRA), PT. XL Axiata Tbk (EXCL), PT. Indofood CBP Sukses Makmur Tbk (ICBP), PT. Vale Indonesia Tbk (INCO), PT. Indofood Sukses Makmur Tbk (INDF), PT. Kalbe Farma Tbk (KLBF), PT. Semen Indonesia (Persero) Tbk (SMGR), PT. Telekomunikasi Indonesia (Persero) Tbk (TLKM), PT. Unilever Indonesia Tbk (UNVR) and PT. Wijaya Karya (Persero) Tbk (WIKA). The levels of risk and return generated from the formed portfolio are: 1) the optimal portfolio approach with the smallest risk has a risk of 1.2% and a return of 0.06%, 2) the optimal portfolio approach with the largest risk has a risk of 3% and a return of 0, 24%, 3) the optimal portfolio approach with short sales has a risk of 1.16% and a return of 0.04%.